ANALYSIS OF LANGUAGE DEVELOPMENT IN CHILDREN AGED 3 YEARS IN KARAWANG: ANALISIS PEMEROLEHAN BAHASA PADA ANAK USIA 3 TAHUN DI KARAWANG - Julaeha (SOSIOEDUKASI, 2024)
This study analyzes the language acquisition of 3 year old children in Karawang. The aim of this research is to analyze the language acquisition of 3 year old children in Karawang. The focus of this research is to understand the language development of children in this age group and the factors that influence it. Research methods used include observational studies and direct recordings. The study was conducted with her 3-year-old child named Ais, who lives in Karawang. The steps that need to be taken when conducting research are direct observation, to observe children's language development in their everyday environment. Record directly to the child to get more information about the language environment at home and the language stimulation given to the child. The results of this study indicate that children aged 3 years in Karawang have different abilities in language acquisition. Some children have reached the stages of perfect word pronunciation and sentence formation, while others are still in the early stages of developing language skills. Factors such as the social environment, language stimuli, and personal factors all influence the language development of these children. This research allows us to better understand language acquisition in 3 year old children in Karawang. The implications of this research can be used to design intervention programs and environmental developments that optimally support children's language development. Further research is also recommended to involve a larger sample and examine other factors that can influence language acquisition in children of Ayes' age.